2020
DOI: 10.1029/2020ja028483
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric Responses at Low Latitudes to the Annular Solar Eclipse on 21 June 2020

Abstract: In this study, we utilized both ground-based and space-borne observations including total electron content (TEC) from Beidou geostationary satellites, two-dimensional TEC maps from the worldwide dense Global Navigation Satellite System receivers, ionosondes, and in situ electron density (Ne) and electron temperature (Te) from both Swarm and China Seismo-Electromagnetic Satellite satellites, to investigate the low-latitude ionospheric responses to the annular solar eclipse on 21 June 2020. The decrease in TEC d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…They also obtained the TEC difference, and their results showed a significant reduction around EIA regions at solar eclipse times. Huang et al (2020) studied the ionospheric responses at low latitudes in a solar eclipse on 21 June 2020. The authors also found that the EIA decreases significantly in the solar eclipse hours.…”
Section: Space Weather Conditions During the Eclipse 2020 Versus Quie...mentioning
confidence: 99%
See 1 more Smart Citation
“…They also obtained the TEC difference, and their results showed a significant reduction around EIA regions at solar eclipse times. Huang et al (2020) studied the ionospheric responses at low latitudes in a solar eclipse on 21 June 2020. The authors also found that the EIA decreases significantly in the solar eclipse hours.…”
Section: Space Weather Conditions During the Eclipse 2020 Versus Quie...mentioning
confidence: 99%
“…Therefore, although this solar eclipse event almost did not reach the equatorial regions, we suppose it was enough to influence the fountain effect. Also, Huang et al (2020) mentioned that during the eclipse events the transequatorial northward or southward neutral wind can weaken, causing a reduction of the EIA crests. Le et al (2009) showed an analysis of the ionosphere in the conjugate hemisphere during the solar eclipse on 3 October 2005.…”
Section: Space Weather Conditions During the Eclipse 2020 Versus Quie...mentioning
confidence: 99%
“…By contrast, the positive TEC deviation appears on the southern side of the obscuration path near 87°–100°E at 0910–0920 UT (Figure 1d). The thermospheric neutral wind flowing toward the obscuration path can lead to the plasma transporting along the magmatic field line at low latitudes (Aa et al., 2021; Cheng et al., 1992; Dang et al., 2020; Huang et al., 2020; Le et al., 2010, 2020; Yeh et al., 1997; Zhang et al., 2020) which can cause the positive TEC deviation in the afternoon (Movie ).…”
Section: Resultsmentioning
confidence: 99%
“…In the ionosphere, aperiodic and quasi-periodic perturbations in the electron density, N, have been detected with a 1 %-10 % amplitude and a ∼ 10 min period, T , whereas the decrease in the electron density of the ionospheric E region attains 26 %, agreeing well with the theoretical estimate (24 %). The solar eclipse of 21 June 2020 that occurred in the equatorial ionosphere was observed by Le et al (2020), Zhang et al (2020), Huang et al ( , 2021, Dang et al (2020), Patel and Singh (2021), J. Wang et al (2021), X.…”
Section: Introductionmentioning
confidence: 81%
“…Wang et al (2021), Şentürk et al (2021), Sun et al (2021), Shagimuratov et al (2021), Aa et al (2021), Chen et al (2021), andTripathi et al (2022); the ionospheric effects were observed to occur with the South Atlantic Anomaly in the background. Zhang et al (2020) detected effects from the solar eclipse in the magnetically conjugate region. Chernogor and Mylovanov (2022) describe the ionospheric effects of the annular solar eclipse of 10 June 2021 that occurred in high latitudes.…”
Section: Introductionmentioning
confidence: 98%